Performance analysis of sustainable reinforced concrete using chemically treated betel nut fiber - Hasan, Mehedi; Tushar, Fazlul Hoque; Hasan, Kamrul; Fadzil, Mat Yahaya; Putra Jaya, Ramadhansyah; Hasan, Rakibul; Sohan, Sahadat Hossain; Rabbani, Md Liton (Elsevier Ltd, 2025)
Natural fiber-reinforced concrete (NFRC) has gained popularity for its renewability, cost-effectiveness, and biodegradability, making it a promising material for construction and repair. Plain concrete has low tensile strength and limited crack resistance, which can be improved by incorporating natural fibers. This research empirically analyzes the effects of low alkali-treated betel nut husk fiber (BNHF) on the fresh, mechanical, and durability properties of NFRC, including workability, density, compressive strength, split tensile strength, water absorption, and failure patterns. It also develops a predictive regression model based on compressive strength results and evaluates BNHF's impact on brittleness, morphology, environmental effects, and cost. In this regard, BNHF fibers (45 mm) were added to plain concrete at 0.50 %, 0.75 %, 1 %, and 1.25 % by binder weight. The results showed a consistent decrease in workability and density, with 1.25 % BNHF exhibiting the highest reduction of 47 % and 4.8 %, respectively, compared to the control mix. However, 1 % BNHF resulted in the highest compressive and split tensile strength, with increases of 43.36 % and 51.61 %, respectively, after 28 days of curing. Water absorption increased with BNHF content due to the fiber's hydrophilic nature. Moreover, BNHF improved concrete brittleness, morphology, and overall performance. Besides, eco-strength efficiency analysis showed a 30.11 % reduction in carbon dioxide (CO2) emissions, while cost analysis indicated a 21.38 % decrease in production costs per MPa for the optimal 1 % BNHF mix. The study concludes that BNHF enhances the strength of NFRC, with higher fiber volumes potentially reducing performance, underscoring its potential as a sustainable and cost-effective reinforcement material.